Effectiveness of project-based learning with cloud tools for developing professional competencies in IT education - Spirina, Yelena; Gorbunova, Nadezhda; Samoilova, Irina; Kazimova, Dinara; Zhumagulova, Saule (Frontiers in Education, 2025)
In accordance with the requirements of the IT sector, higher education is aimed at training IT specialists with relevant hard and soft skills competencies. This study examines the possibility of integrating Project-Based Learning (PBL) into training of IT students to develop programming, project and teamwork skills using professional cloud services and tools in IT project work. The selection of relevant cloud tools for project work was carried out by an expert group of teachers and IT specialists. The proposed approach was applied when studying programming courses at the Karaganda Buketov University. The students of the experimental group studied using PBL and professional cloud tools to work on the project, depending on the tasks and type of project. Pre- and post-testing were used for quantitative analysis, and surveys were conducted for qualitative analysis to assess students’ programming skills, project activities, and teamwork before and after the experiment. The experimental group showed positive results in statistical data analysis, which indicates the effectiveness of the methods used. Based on the obtained experimental data and analysis of existing scientific works, conclusions were made confirming the relevance and effectiveness of the implementation of PBL with cloud services in the educational process in IT disciplines in higher education.